1998
DOI: 10.1007/s007050050404
|View full text |Cite
|
Sign up to set email alerts
|

Critical amino acid changes in VP2 variable domain are associated with typical and atypical antigenicity in very virulent infectious bursal disease viruses

Abstract: Classical serotype 1 infectious bursal disease viruses (IBDV), but not very virulent (vv) isolates, react with neutralizing monoclonal antibody (NMab) 3 in virus neutralization tests or antigen-capture ELISA. Two other NMabs, 6 and 8, bind to both classical and most vv strains, but not to the atypical 94,432 and 91,168 vv strains, respectively. The basis for such reactivities was investigated by sequencing the genome region encoding the VP2 major immunogenic domain. In classical, variant, vaccine or vv IBDV st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 18 publications
7
73
0
4
Order By: Relevance
“…(Bygrave & Faragher, 1970), used as a reference for the ''classical'' IBDVs, and with the 91168 and 94432 atypical vvIBDV strains (Eterradossi et al, 1997b(Eterradossi et al, , 1998. The Faragher 52/70 virus reacted strongly with all mAbs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(Bygrave & Faragher, 1970), used as a reference for the ''classical'' IBDVs, and with the 91168 and 94432 atypical vvIBDV strains (Eterradossi et al, 1997b(Eterradossi et al, , 1998. The Faragher 52/70 virus reacted strongly with all mAbs.…”
Section: Resultsmentioning
confidence: 99%
“…Dots indicate positions where the sequence is identical to F52/70. The sequence of the antigenically atypical vvIBDV isolates 91168 and 94432 (Eterradossi et al, 1998) has been indicated for comparative purposes. VP2 major and minor hydrophilic peaks are boxed with or without grey shading, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations